Anisotropic transmissive coding metamaterials based on dispersion modulation of spoof surface plasmon polaritons. (24th May 2018) - Pang, Yongqiang; Li, Yongfeng; Zhang, Jieqiu; Chen, Hongya; Xu, Zhuo; Qu, Shaobo
Abstract: Anisotropic transmissive coding metamaterials (CMMs) have been designed and demonstrated in this work. High-efficiency transmission with the amplitudes close to unity is achieved by ultrathin metallic tapered blade structures, on which incident waves can be highly coupled into spoof surface plasmon polaritons (SSPPs). The transmission phase can be therefore manipulated with much freedom by designing the dispersion of the SSPPs. These tapered blade structures are designed as the anisotropic unit cells of the CMMs. Two 1-bit anisotropic CMMs with different coding sequences were first designed and simulated, and then a 2-bit anisotropic CMM was designed and measured experimentally. The measured results agree well with the simulations. It is expected that this work provides an alternative method for designing the transmissive CMMs, and may find potential applications in the beam forming technique.